2014
DOI: 10.1074/jbc.m113.517581
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Inhibits COX-2 Expression and Inflammatory Response by Targeting Thioesterase Superfamily Member 4

Abstract: Background: Vitamin D insufficiency has been associated with chronic inflammatory diseases. However, the underlying mechanisms remain unclear. Results: Vitamin D inhibits COX-2-mediated inflammatory response by modulating the Akt/NF-B signaling pathway via direct up-regulation of thioesterase superfamily member 4. Conclusion: Vitamin D plays novel roles in anti-inflammation. Significance: Supplemental vitamin D could protect against chronic inflammatory diseases by targeting THEM4/Akt/NF-B signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(78 citation statements)
references
References 59 publications
6
71
0
1
Order By: Relevance
“…34 The present study analyzed serum IL-10 level in LPS-treated mice. 42,43 Another in vitro study showed that active VitD3 repressed excess NO production in LPS-stimulated macrophages. These results are in Several reports demonstrated that excess PGs and NO play important roles in LPS-induced adverse pregnant outcomes including fetal demise, abortion, and preterm delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 The present study analyzed serum IL-10 level in LPS-treated mice. 42,43 Another in vitro study showed that active VitD3 repressed excess NO production in LPS-stimulated macrophages. These results are in Several reports demonstrated that excess PGs and NO play important roles in LPS-induced adverse pregnant outcomes including fetal demise, abortion, and preterm delivery.…”
Section: Discussionmentioning
confidence: 99%
“…20,21,43 According to an in vitro study, active VitD3 blocked TNFα-mediated nuclear translocation of NF-κB p65 subunit through reinforcing interaction between VDR and IκB kinase β in HEK293 cells. 20,21,43 According to an in vitro study, active VitD3 blocked TNFα-mediated nuclear translocation of NF-κB p65 subunit through reinforcing interaction between VDR and IκB kinase β in HEK293 cells.…”
Section: Discussionmentioning
confidence: 99%
“…One of the actions of Vitamin D is to inhibit IL-12 [309,312], which helps to promote the development of the Th1 cells described earlier. Vitamin D may also reduce macrophage-mediated inflammatory processes by repressing the expression of cyclooxygenase-2 (COX-2) and increasing expression of thioesterase superfamily member 4 (THEM4), which is a negative regulator of Akt [313]. Just how Vitamin D acts to maintain the normal function of the dendritic cells is not clear, but there are indications that it may depend on its role as a guardian of the Ca 2þ and ROS signalling pathways.…”
Section: Vitamin D In Adaptive Immunity and Autoimmune Diseasesmentioning
confidence: 96%
“…An important target of 1,25(OH) 2 D 3 is thioesterase superfamily member 4 (THEM4), an inhibitor of the NFκB signaling pathway. THEM4 inhibits the direct binding of NFκB to the COX-2 locus and thereby prevents COX-2 transcription (106). Furthermore, THEM4 inhibits IL-6 and TNFα expression by preventing the signaling cascade in which NFκB induces miR-155 to suppress SOCS (105).…”
Section: Immune Modulation By Vitamin Dmentioning
confidence: 99%